Effects of sectoral components of economic growth, gender and public expenditure composition on poverty in Nigeria - Mustapha, Alhaji Bakar (2016)
This study investigates three independent but related issues.First, it examines the effects of sectoral components of economic growth on poverty in Nigeria. It is generally agreed that economic growth, which is supported by structural change, would lead to rapid poverty reduction. The study employs static panel data regression to analyze the data. The results show that rural agricultural growth and urban wholesale/retail sector growth exert significant influence on poverty reduction, while growth in the industrial and services sectors has less influence on poverty reduction.In general, the change in the structure of the economy has not been effective in reducing poverty in Nigeria. The results also do not seem to suggest that the low poverty reduction of the structural change is associated with income inequality. Thus, there is a need for policies directed towards expanding investment in the agricultural and the labor-intensive export manufacturing sector to complement the agricultural sector. The second objective of the study examines the impact of gender and socioeconomic characteristics of household heads on poverty in Nigeria. Logistic regression techniques are employed to analyze the data. The results show that the chances of households being poor are lower for female-maintained families and households with high female-to-male ratios, while larger household size and high dependency ratios increase the chances of household heads being poor. Therefore, the analyses of the results do not warrant leaving male-headed families out of the special anti-poverty programs. The third objective is to investigate the effects of public expenditure composition via growth, employment and wages on poverty reduction. This will help in identifying the most effective pro-poor sectors for the efficient allocation of scarce resources. The study uses Seemingly Unrelated Regression (SUR) techniques. The results show that public expenditure on education, health and agriculture exerts a positive impact on poverty. The study also indicates that the public expenditure categories have directly and indirectly affected the rate of poverty while the indirect effects of transport and infrastructure expenditure are insignificant. The study concludes that for the effective performance of public expenditure, there is a need to increase the proportion of the investment part of the expenditure.